PEMANFAATAN DAN PELAPORAN ANJAK PIUTANG (FACTORING) - Emita Wahyu Astami (Journal of Indonesian Economy and Business (JIEB), 2000)
Factoring is the purchases of a firm’s accounts receivables (the client) by another firm (the factor) for a discount fee. This paper attempts to discuss the benefit of factoring receivables, steps taken to avoid serious problems that can arise from factoring, and reporting the sales of receivables.Being successful in the future, a company will probably need to sell overseas and being global, therefore it needs to work with an international factoring company. By using the services provided by a factor, the client gains a partner who can provide administration, working capital enhancement, business experience, and overall guidance in selling products abroad. Factors can be considered to become the receivable management entities therefore, management can focus on developing, producing, and selling products.However, before entering into a factoring agreement, a firm need to consider and take steps to avoid risks. Factoring programs work only if both factors and clients pay adequate attention to preventing problems before they arise.Finally, both the client and the factor need to report factoring receivables based on Statement on Financial Accounting Standards (PSAK) No. 43. In a factoring, receivables are sold on either a without recourse or a with recourse basis.